1995
DOI: 10.1524/ract.1995.68.4.245
|View full text |Cite
|
Sign up to set email alerts
|

Retardation of Technetium and Iodine by Antimony- and Mercury-Containing Minerals

Abstract: The retardation of technetium by an antimony-containing mineral, stibnite, and of iodine by a mercury-containing mineral, tiemannite, has been studied using column experiments. Data are presented and possible retardation mechanisms are discussed.The addition of as little as 10% of stibnite to a column of crushed granite was found to be sufficient to retard the transport of technetium through the column. The effect of flow rate on the retardation of technetium was considerable: at a linear velocity of 3 cm/h, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…However, under reducing conditions, and in the absence of complexing agents, the tetravalent Tc(IV) ion dominates (Francis et al 2002). In this oxidation state, 99 Tc is relatively immobile and can form highly insoluble minerals like TcO 2 and strong complexes on Al, Fe, and Sb oxides as well as on clays (Lieser and Bauscher 1987;Meyer et al 1991;Haines et al 1987;Zhaung et al 1995). Such changes can be mediated by abiotic and/or biotic processes.…”
Section: Degradation/transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, under reducing conditions, and in the absence of complexing agents, the tetravalent Tc(IV) ion dominates (Francis et al 2002). In this oxidation state, 99 Tc is relatively immobile and can form highly insoluble minerals like TcO 2 and strong complexes on Al, Fe, and Sb oxides as well as on clays (Lieser and Bauscher 1987;Meyer et al 1991;Haines et al 1987;Zhaung et al 1995). Such changes can be mediated by abiotic and/or biotic processes.…”
Section: Degradation/transformationmentioning
confidence: 99%
“…In this oxidation state, 99 Tc is relatively immobile and can form highly insoluble minerals like TcO 2 , as well as strong complexes on Al, Fe, and Sb oxides as well as clays (Lieser and Bauscher 1987;Meyer et al 1991;Haines et al 1987;Zhaung et al 1995).…”
Section: Bulk Density and Distribution Coefficientmentioning
confidence: 99%
“…These anionic species are of serious concem because their migration is poorly retarded by geological materials such as kaolinite, montmorillonite and granite [3][4][5]. Several researchers have focused on the sorption studies of anionic species on inorganic sorbents [6][7][8][9][10]. It has been suggested that technetium can be sorbed on minerals containing iron or sulfide by reducing TCO4 to TcOzCs) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have focused on the sorption studies of anionic species on inorganic sorbents [6][7][8][9][10]. It has been suggested that technetium can be sorbed on minerals containing iron or sulfide by reducing TCO4 to TcOzCs) [7][8][9]. In the iodine sorption studies, mercury-or sulfide-containing minerals show a high capacity for the retardation of [3,10].…”
Section: Introductionmentioning
confidence: 99%
“…Tc attenuation performance of sulfide minerals is highly variable and appears to depend on a number of factors, such as the type of mineral, particle size, type of contacting solution, pH, ionic strength, and Eh (Balsley et al 1997, Fried et al 1978Lee and Bondietti 1983, Lieser and Bauscher 1988, Palmer and Meyer 1981, Strickert et al 1980Zhuang et al 1988, Zhuang et al 1995. It is generally recognized that the principal mechanisms of 99 Tc attenuation by sulfide minerals are through either reduction of Tc(VII) to low-solubility Tc(IV) phases such as TcO 2 ·x H 2 O or by direct precipitation of Tc(VII) as the sparingly soluble sulfide mineral Tc 2 S 7 (Bidoglio and Plano 1985, Lee and Bondietti 1983, Lieser and Bauscher 1988.…”
Section: Published Data Indicate That the 99mentioning
confidence: 99%